2021
DOI: 10.7759/cureus.18755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vivo Adhesion Properties of New Generation Polyglactin, Oxidized Regenerated Cellulose and Chitosan-Based Meshes for Hernia Surgery

Abstract: IntroductionComposite meshes coated with anti-adhesive barriers have been developed by taking advantage of the robustness of polypropylene meshes for use in hernia repair. We aimed to evaluate the effects of composite meshes containing polyglactin, polycaprolactone, oxidized regenerated cellulose and chitosan on the adhesion formation. MethodsForty-two Sprague Dawley male rats were divided into six groups of seven rats according to the content of the meshes used. A defect was created on the right abdominal wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[61] Common derivatives include carboxymethylcellulose (CMC), [123][124][125] methylcellulose (MC), [97] and oxidized regenerated cellulose (ORC). [126][127][128] In recent years, the application of bacterial cellulose (BC) in the fabrication of advanced AWHPMs has been significantly attractive. [61,129,130] BC produced by bacteria (e.g., Komagataeibacter xylinus X-2 [59] ) has a linear structure comprised of beta-1,4-glucan chains.…”
Section: Carbohydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] Common derivatives include carboxymethylcellulose (CMC), [123][124][125] methylcellulose (MC), [97] and oxidized regenerated cellulose (ORC). [126][127][128] In recent years, the application of bacterial cellulose (BC) in the fabrication of advanced AWHPMs has been significantly attractive. [61,129,130] BC produced by bacteria (e.g., Komagataeibacter xylinus X-2 [59] ) has a linear structure comprised of beta-1,4-glucan chains.…”
Section: Carbohydratesmentioning
confidence: 99%
“…[101] Widely employed in tissue recovery applications, [133] CTS owes its popularity to its extraordinary antibacterial properties [99,101] and biodegradability. [76] Several studies have demonstrated inadequate blood compatibility of CTS/CTS-based materials used in AWR, [128,134,135] leading to acute and chronic inflammation, [76,99] and hindering the wound healing process. [99] Additionally, CT and its derivatives suffer from hydrophobicity and restricted solubility in water within the context of AW application.…”
Section: Carbohydratesmentioning
confidence: 99%